Aggregation‐Induced Emissive Carbon Dots Gels for Octopus‐Inspired Shape/Color Synergistically Adjustable Actuators. Issue 40 (25th August 2021) - Wu, Shuangshuang; Shi, Huihui; Lu, Wei; Wei, Shuxin; Shang, Hui; Liu, Hao; Si, Muqing; Le, Xiaoxia; Yin, Guangqiang; Theato, Patrick; Chen, Tao
Abstract: Some living organisms such as the octopus have fantastic abilities to simultaneously swim away and alter body color/morphology for disguise and self‐protection, especially when there is a threat perception. However, it is still quite challenging to construct artificial soft actuators with octopus‐like synergistic shape/color change and directional locomotion behaviors, but such systems could enhance the functions of soft robotics dramatically. Herein, we proposed to utilize unique hydrophobic carbon dots (CDs) with rotatable surficial groups to construct the aggregation‐induced emission (AIE) active glycol CDs polymer gel, which could be further employed to be interfacially bonded to an elastomer to produce anisotropic bilayer soft actuator. When putting the actuator on a water surface, glycol spontaneously diffused out from the gel layer to allow water intake, resulting in a color change from a blue dispersion fluorescence to red AIE and a shape deformation, as well as a large surface tension gradient that can promote its autonomous locomotion. Based on these findings, artificial soft swimming robots with octopus‐like synergistic shape/color change and directional swimming motion were demonstrated. This study provides an elegant strategy to develop advanced multi‐functional bio‐inspired intelligent soft robotics. Abstract : Carbon dots (CDs) with rotatable symmetric surfaces were used to develop aggregation‐induced emissive CD polymer gels with reversible two‐switch‐mode fluorescence (blue dispersed fluorescence and red AIE), followed by the fabrication of anisotropic swimming robots showing octopus‐like synergistic shape/color change and autonomous locomotion on the water surface.